СЕЛЬСКОЕ ХОЗЯЙСТВО КАРАКАЛПАКСТАНА В 1985-1990 гг. ЧАСТЬ I. ПРОЦЕССЫ ФОРМИРОВАНИЯ НОВЫХ ЭКОНОМИЧЕСКИХ ОТНОШЕНИЙ - Сарыбаев, М.К. (SCIENCE and SOCIETY, 2024)
The article reveals the prosess of formation of new economic relations on agroculture of Karakalpakstan in second half of 80 years of ХХ th century.